Structural and genomic evolutionary dynamics of Omicron variant of SARS-CoV-2 circulating in Madhya Pradesh, India - Dhankher, Suman; Yadav, Pooja; Sharma, Shashi; Gupta, Ekta; Yadav, Ram Govind; Dash, Paban Kumar; Parida, Manmohan (Frontiers in Medicine, 2024)
The SARS-CoV-2 Omicron (B.1.1.529) variant emerged in early November 2021 and its rapid spread created fear worldwide. This was attributed to its increased infectivity and escaping immune mechanisms. The spike protein of Omicron has more mutations (>30) than any other previous variants and was declared as the variant of concern (VOC) by the WHO. The concern among the scientific community was huge about this variant, and a piece of updated information on circulating viral strains is important in order to better understand the epidemiology, virus pathogenicity, transmission, therapeutic interventions, and vaccine development. A total of 710 samples were processed for sequencing and identification up to a resolution of sub-lineage. The sequence analysis revealed Omicron variant with distribution as follows: B.1.1, B.1.1.529, BA.1, BA.2, BA.2.10, BA.2.10.1, BA.2.23, BA.2.37, BA.2.38, BA.2.43, BA.2.74, BA.2.75, BA.2.76, and BA.4 sub-lineages. There is a shift noted in circulating lineage from BA.1 to BA.2 to BA.4 over a period from January to September 2022. Multiple signature mutations were identified in S protein T376A, D405N, and R408S mutations, which were new and common to all BA.2 variants. Additionally, R346T was seen in emerging BA.2.74 and BA.2.76 variants. The emerging BA.4 retained the common T376A, D405N, and R408S mutations of BA.2 along with a new mutation F486V. The samples sequenced were from different districts of Madhya Pradesh and showed a predominance of BA.2 and its variants circulating in this region. The current study identified circulation of BA.1 and BA.1.1 variants during initial phase. The predominant Delta strain of the second wave has been replaced by the Omicron variant in this region over a period of time. This study successfully deciphers the dynamics of the emergence and replacement of various sub-lineages of SARS-CoV-2 in central India on real real-time basis.